Hacer de las Memorias una experiencia. Otras formas de registrar el pasado - Clementina Battcock (Nuevo mundo - Mundos Nuevos, 2018)
In this paper I explore different forms of knowledge, often ignored by the western reason: the systems of knowledge of the indigenous people of America.I Will take this systems o knowledge like points of convergence of an ancestral memory, and also like a memory created by the experience of the past and present of the Américan indigenous people as plural and changing subjects. I will take the importance of the comunity the most important space of reference for the indigenous konowledge, and i will analyze the relationship with nature, because this is the mechanism that they use to reproduce their culture and reapropiate their enviroment. We can´t take off the agency of this people and we should think about categories like subalternity.